Perbandingan karakteristik shock breaker standar dan modifikasi pada sepeda motor - I Made Parwata; IGN Nitya Santhiarsa; Benatyar - (Department of Mechanical Engineering, University of Udayana, 2006)
During driving, vibration is one of some comfortable point. Vibration can appear as the result of road surface beside itsengine vibration. To decrease vibration caused road surface the vehicle was completed with shock breaker. This experiment was conducted in order to investigate the effect of vibration on the comfortable in driving. The shock breaker and body of vehicle will be modeled in single degree of freedom in the vibration system. By using two-model shock breaker standard and modification hence the model was tested, and then the results were applied to Janeway criteria to examine its comfortable. From both the experiment and calculation, it was found that the amplitude of standard and modification shock breakerexceeded the maximum allowable amplitude of Janeway comfortable criteria.